Government Expenditure on Education and Health: Islamic Economic Perspective on Poverty Alleviation in Lampung Province (2018-2022) - Irmayanti, Lulu; Hayati, Mardhiyah; Supriyaningsih, Okta (Institut Agama Islam Negeri Kendari, 2024)
Difficulties in accessing education and health services are at the root of poverty. The purpose of this research is to determine the impact of expenditure on education and health on poverty in Lampung Province 2018-2022 while considering the perspectives of Islamic economics. The method in this research uses a quantitative. The results of this research show that if government spending in the education sector increases, the poverty rate will increase. If the health sector increases, the poverty rate will decrease. If both increase, poverty will be affected. Government spending in education and health is in line with the principles of Islamic economics Al-Adl (justice), which implement fair and trustworthy policies, such as the regional government in Lampung Province always increasing budget and service facilities so that poverty in Lampung Province can decrease every year.